2022
DOI: 10.1055/a-1953-6317
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Musculoskeletal Injury in CrossFit: A Systematic Review

Abstract: The objective of this systematic review was to identify potential risk factors for injury in CrossFit participants. Embase, Medline, Web of Science, Cochrane, CINAHL, Google Scholar, and SportDiscuss databases were all searched up to June 2021. Cohort studies that investigated risk factors for CrossFit injuries requiring medical attention or leading to time-loss in sports were included. A best evidence synthesis was performed combining all the outcomes from prospective cohort studies. From 9,452 publications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Currently, CrossFit ® practice has increased as has the number of publications related to the characteristics of the associated injuries [15][16][17]. Furthermore, it has been studied all across the world in countries such as Portugal, Brazil and the Netherlands [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CrossFit ® practice has increased as has the number of publications related to the characteristics of the associated injuries [15][16][17]. Furthermore, it has been studied all across the world in countries such as Portugal, Brazil and the Netherlands [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…To date, authors have examined a range of research areas surrounding the sport of CrossFit ® in several literature reviews [ 6 ]. The focus is usually on short- and long-term physiological responses [ 7 , 8 , 9 , 10 , 11 ], nutritional strategies or interventions [ 12 , 13 ], psychological parameters [ 14 , 15 , 16 , 17 , 18 ], and musculoskeletal injury risks of the training program [ 19 , 20 , 21 , 22 , 23 , 24 ]. Additionally, research on related training routines, such as high-intensity functional training (HIFT) [ 25 ] or high-intensity multimodal training (HIMT) [ 26 ] helps to determine how the training concept of CrossFit ® is practiced and applied.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the potential high injury risk of CrossFit ® [20][21][22]. Recently, a systematic review has shown a positive influence on body composition and physical fitness [17] in CrossFit ® practitioners.…”
Section: Introductionmentioning
confidence: 99%